Clinical Value of Cytokine Assay in Diagnosis and Severity Assessment of Lung Cancer. (9th August 2022) - Ma, Jin; Zhu, Shumin; Liu, Zining; Mao, Yafei; Li, Xinyuan; Dai, Lili; Zhao, Xiaojie; Wei, Congzhen; Liu, Jinfeng; Geng, Yulan
Abstract : Purpose . To investigate the clinical value of interleukin 2 (IL-2), interleukin 4 (IL-4), interleukin 6 (IL-6), interleukin 10 (IL-10), tumor necrosis factor α (TNF- α ), and interferon- γ (IFN- γ ) in diagnosis and severity assessment of lung cancer. Methods . In this observational study, 50 physical examination healthy subjects were included in the control group and 100 lung cancer patients were included in the study group. In the study group, 53 cases with pleural effusion were subgrouped to the pleural effusion group ( n  = 53), while 47 patients were assigned to the nonpleural effusion group ( n  = 47). Plasma cytokines IL-2, IL-4, IL-6, IL-10, TNF- α, IFN- γ, and Acute Physiology and Chronic Health Evaluation II (APACHE II) scores of all eligible subjects were collected and compared. Results. The study group showed significantly higher levels of plasma cytokines IL-2, IL-4, IL-6, IL-10, TNF- α, and IFN- γ versus healthy subjects (P < 0.05 ). Deterioration of lung cancer was associated with increased plasma cytokine levels and APACHE II scores. The combination assay of the above plasma cytokines showed significantly better diagnostic efficacy for lung cancer versus the single assay of the cytokines. Dead patients had higher plasma cytokine levels versus survived patients. The accuracy of plasma IL-2, IL-4, IL-6, IL-10, TNF- α, and IFN- γ levels in the severity assessment of lung cancer was comparable with that of the APACHE II scale. Conclusion . The plasma cytokines IL-2, IL-4, IL-6, IL-10, TNF- α, and IFN- γ are effective markers for the diagnosis of lung cancer. The combined assay contributes to the early diagnosis of lung cancer patients, and the persistent elevation of cytokines suggests an increased risk of death in lung cancer patients, so the detection of cytokine levels facilitates the severity assessment of lung cancer.